2018
DOI: 10.1248/bpb.b18-00444
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Eye Disorders Caused by Paclitaxel: A Retrospective Study

Abstract: Paclitaxel and nanoparticle albumin-bound paclitaxel are known to cause adverse events of eye disorders, such as cystoid macular edema. However, at present, the risk factors remain unclear. Therefore, risk factors for eye disorders caused by paclitaxel and nanoparticle albumin-bound paclitaxel were studied. This retrospective study targeted patients who were newly administered paclitaxel or nanoparticle albumin-bound paclitaxel at Kyoto Okamoto Memorial Hospital between April 1, 2012, and March 31, 2017. Eye d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…We previously reported that visual acuity reduction caused by PTX occurred in 2.3% of patients, and no cases of cystoid macular edema were noted. 5 No cases of cystoid macular edema were noted even in the present study. However, visual acuity reduction or blurred vision may be an early symptom of cystoid macular edema.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…We previously reported that visual acuity reduction caused by PTX occurred in 2.3% of patients, and no cases of cystoid macular edema were noted. 5 No cases of cystoid macular edema were noted even in the present study. However, visual acuity reduction or blurred vision may be an early symptom of cystoid macular edema.…”
Section: Discussioncontrasting
confidence: 53%
“…The evaluation of adverse events was performed as follows: (1) Pharmacists asked the patient about the occurrence of general adverse events; (2) For typical adverse events, such as nausea and edema, pharmacists confirmed the presence or absence of the symptoms and severity of the symptoms by closed questions; (3) For other adverse events, pharmacists confirmed by open questions, such as ''Have you experienced a change in your physical condition? ''; (4) If patients complained about eye disorders, pharmacists confirmed the time of onset of symptoms and details of symptoms; (5) Pharmacists reported to the doctor and requested the doctor to consult with the ophthalmologist or pharmacists advised patients to undergo an ophthalmology consultation; and (6) The ophthalmologist diagnosed eye disorders.…”
Section: Definition Of Eye Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found the association between cryotherapy and lower CIPN20 autonomic scores, although they concluded that clinical relevance was unlikely (19). Autonomic symptoms were infrequently reported and rarely considered cardinal adverse effects of paclitaxel (36,37). Potentially, the observed improvement in SSR and CIPN20 autonomic subscale could be the inherent effect of cryotherapy, regardless of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Alkylating agent/platinum Blurred vision, retinotoxicity (retinal ischaemia and neovascularization), optic neuropathy [33] Doxorubicin anthracyline drug conjunctivitis (m/c), periorbital edema, lacrimation, blepharospasm, keratitis, and decreased visual acuity [34] Everolimus mTOR inhibitor posterior reversible encephalopathy syndrome,bilateral optic neuropathy [35] Geftinib EGFR-inhibitor Dry eye, corneal ulcer [36,37] Gemcitabine antimetabolite agent uveal effusion and outer retinal disruption or Purtscher-like retinopathy with combination of docetaxel [25,38] Irinotecan topoisomerase I inhibitor None [39], none in combination regimen with 5-fluorouracil, oxaliplatin and bevacizumab [40] Oxaliplatin platinum dry eye, lacrimation, conjunctivitis, damage of the retinal pigment epithelium and the optic nerve, visual field defect [30,41] Paclitaxel Antimicrotubule agent epiphora, eye pain, conjunctivitis, blepharitis, blurred vision [24,42] Pemetrexed Antimetabolite /antifolate AION [1], eyelid edema [24,43] Ramucirumab monoclonal Ab of VEGFR-2 none [28] Sorafenib anti-VEGF agent blurred vision, periocular edema, retinal detachment, ptosis, optic neuropathy, macular edema [27,44] Temozolomide alkylating/methylating agent blurred vision with concurrent radiation therapy [45].…”
Section: Cisplatinmentioning
confidence: 99%